Green Technologies and RFID: Present and Future - Orecchini, Giulia; Alimenti, Federico; Roselli, Luca; Yang, Li; Rida, Amin; Tentzeris, Manos M. (Applied Computational Electromagnetics Society Journal (ACES), 2022)
RFID systems are proliferating in everyday applications. In this paper, the authors present a unified approach that relies on the development of novel low-cost inkjet-printed platforms with optimized metallization trace and effective integration of diodes for enhanced discrimination capability applications. Potentially, the presented approach could set the foundation for the first generation of truly “green” RFIDbased devices.